2010
DOI: 10.1007/s12024-009-9140-6
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of Armanni–Ebstein phenomenon at autopsy

Abstract: A 41-year-old woman with a past history of insulindependent diabetes mellitus, intravenous drug use and asthma was found collapsed and unresponsive at her home address. Her history also included previous hospital admissions with diabetic ketoacidosis. She was conveyed by ambulance to hospital, where she was found to be unconscious, hypotensive and acidotic with a markedly elevated blood glucose level. Resuscitative efforts were unsuccessful.At autopsy, the most significant finding was of marked pallor of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Neilson, Thomsen and colleagues further examined these lesions and reported that the vacuoles contained fat [4,5]. In 2010 Byard also recorded fat in the lesions and pointed out that a clue to the diagnosis is the macroscopic appearance of the cortex with pallor present [15]. The same appearance may be seen in cases of alcoholic ketoacidosis (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Neilson, Thomsen and colleagues further examined these lesions and reported that the vacuoles contained fat [4,5]. In 2010 Byard also recorded fat in the lesions and pointed out that a clue to the diagnosis is the macroscopic appearance of the cortex with pallor present [15]. The same appearance may be seen in cases of alcoholic ketoacidosis (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Thomsen and colleagues reported that the vacuoles in Armanni-Ebstein lesion contained fat [5,6]. In 2010 Byard also recorded fat in the lesions and pointed out that a clue to the diagnosis is the macroscopic appearance of the cortex with pallor present [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the reported case significant tubular vacuolization was present, to such an extent that it was first identified macroscopically [13], and this was associated with Wischnewsky spots indicating hypothermia. Diabetic ketoacidosis was, however, subsequently identified biochemically by testing of vitreous humor for glucose, lactate and b-hydroxybutyrate.…”
Section: Discussionmentioning
confidence: 54%